Targeting Fructosamine Oxidase (Amadoriase II) in Aspergillus fumigatus: Comprehensive Virtual Screening, ADMET Analysis, and Molecular Dynamics Simulation of Triazole Derivatives - Yamari, Imane; Abchir, Oussama; Khedraoui, Meriem; Errougui, Abdelkbir; Talbi, Mohammed; Samadi, Abdelouahid; El Kouali, MHammed; Chtita, Samir (Current Medicinal Chemistry, 2026)
IntroductionAspergillus fumigatus, a significant fungal pathogen, poses a threat to human health, especially in immunocompromised individuals. Addressing the need for novel antifungal strategies, this study employs virtual screening to identify potential inhibitors of Fructosamine oxidase, also known as Amadoriase II, a crucial enzyme in Aspergillus fumigatus (PDB ID: 3DJE).MethodsVirtual screening of 81,197 triazole derivatives was subjected to computational analysis, aiming to pinpoint molecules with high binding affinity to the active site of Fructosamine oxidase. Subsequently, an in-depth ADMET analysis assessed the pharmacokinetic properties of lead compounds, ensuring their viability for further development. Molecular dynamics simulations were performed to evaluate the stability of top-ranked compounds over time.ResultsThe results unveil a subset of triazole derivatives displaying promising interactions, suggesting their potential as inhibitors for further investigation.ConclusionThis approach contributes to the development of targeted antifungal agents, offering a rational starting point for experimental validation and drug development against Aspergillus fumigatus infections.
Keywords: Aspergillus fumigatus